Numerical Simulation of an Air Pollution Model on Industrial Areas by Considering the Influence of Multiple Point Sources - Pravitra Oyjinda; Nopparat Pochai (My University, 2019)
A numerical simulation on a two-dimensional atmospheric diffusion equation of an air pollution measurement model is proposed. The considered area is separated into two parts that are an industrial zone and an urban zone. In this research, the air pollution measurement by releasing the pollutant from multiple point sources above an industrial zone to the other area is simulated. The governing partial differential equation of air pollutant concentration is approximated by using a finite difference technique. The approximate solutions of the air pollutant concentration on both areas are compared. The air pollutant concentration levels influenced by multiple point sources are also analyzed.
Keywords: Industrial area; Point source; Atmospheric aerosols and clouds